Researches of the imidazole and indole derivatives cerebroprotective activity and its impact on effects of antidepressants - I. I. Abramets; T. O. Zayka; D. V. Evdokimov; Y. V. Kuznetsov; Y. V. Sidorova (LLC "Publisher OKI", 2020)
Background. Treatment of depression disorders is insufficiently effectively. It uses for increasing of treatment efficiency empirical selected combinations of antidepressants with preparations of lithium and certain others, which possess cerebroprotective aside from psychopharmacological activity. Purpose. A study the spectrums of cerebroprotective activity of derivatives of benzimidazole - diacamph and of pyrrolo-oxindole - substance R-86 and referent preparation piracetam as well as its impact on ability of antidepressants to weaken the manifestation of behavioral depression evoked by chronic inflammation.Methods. It was investigated on slices of dorsal hippocampus in vitro by means of electrophysiological methods the impact of administrated during 10 days diacamph, substance R-86 and piracetam on evoked by deprivation of oxygen and glucose, 1 mM H2O2 and 50 pM N-methyl-D-aspartate damages of pyramidal neurons. It was simulates in experiments in vivo behavioral depression evoked by chronic inflammationand researched impact of diacamph, substances R-86 and piracetam on evoked by antidepressants weakening of behavioral depression main manifestations.Results. It was ascertained, that chronic i/p administration diacamph, substance R-86 (10 mg/kg) and piracetam (100 mg/kg) rats reduced damages of hippocampal pyramidal neurons evoked by oxygen/glucose deprivation, oxidative stress and N-methyl-D-aspartate, i. e. drugs possess by cerebroprotective activity. In behavioral experiments investigate potentiating influence of diacamph and substance R-86 on affected imipramine, amitryptiline and ketamine duration of immobilization and marker of preference sucrose solution in rat behavioral depression evoked by chronic inflammation.Conclusion. Drugs with cerebroprotective action potentiate effects of traditional and fast-acting antidepressants.